A discourse analysis of corruption instituting neoliberalism against corruption in Albania, 1998-2005 - Kajsiu, Blendi (Southeast European studies, 2016)
Why did Albania enjoy some of the most successful anti-corruption programs and institutions along with what appeared to be growing levels of corruption during the period 1998-2005? Looking at corruption through a post-structuralist discourse analysis perspective this book argues that the dominant corruption discourse in Albania served primarily to institute the neoliberal order rather than eliminate corruption. As a rare example of post-structuralist discourse analysis of corruption this book can be useful for future research on discourses of corruption in other countries of the region and beyond.